Measuring beta‐galactose exposure on platelets: Standardization and healthy reference values. Issue 5 (2nd June 2020) - Lasne, Dominique; Pascreau, Tiffany; Darame, Sadyo; Bourrienne, Marie‐Charlotte; Tournoux, Peggy; Philippe, Aurélien; Ziachahabi, Sara; Suarez, Felipe; Marcais, Ambroise; Dupont, Annabelle; Denis, Cécile V.; Kauskot, Alexandre; et al.
Abstract: Background: Correct diagnosis of the cause of thrombocytopenia is crucial for the appropriate management of patients. Hyposialylation/desialylation (characterized by abnormally high β‐galactose exposure) accelerates platelet clearance and can lead to thrombocytopenia. However, the reference range for β‐galactose exposure in healthy individuals has not been defined previously. Objective: The objective of the present study was to develop a standardized assay of platelet β‐galactose exposure for implementation in a clinical laboratory. Methods: β‐Galactose exposure was measured in platelet‐rich plasma by using flow cytometry and Ricinus communis agglutinin (RCA). A population of 120 healthy adults was recruited to study variability. Results: We determined an optimal RCA concentration of 12.5 μg/mL. The measure was stable for up to 4 hours (mean fluorescence intensity [MFI]‐RCA: 1233 ± 329 at 0 hour and 1480 ± 410 at 4 hours). The platelet count did not induce a variation of RCA and the measure of RCA was stable when tested up to 24 hours after blood collection (MFI‐RCA: 1252 ± 434 at day 0 and 1140 ± 297 24 hours after blood sampling). To take into account the platelet size, results should be expressed as RCA/forward scatter ratio. We used the assay to study variability in 120 healthy adults, and we found that the ratio is independent of sex and blood group. Conclusion: We defined a normal range in a healthy population and several preanalytical and analytical variables were evaluated, together with positive and negative controls. This assay may assist in the diagnosis of thrombocytopenic diseases linked to changes in β‐galactose exposure.